2015
DOI: 10.1016/j.molp.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

A Small Multifunctional Pentatricopeptide Repeat Protein in the Chloroplast of Chlamydomonas reinhardtii

Abstract: Organellar biogenesis is mainly regulated by nucleus-encoded factors, which act on various steps of gene expression including RNA editing, processing, splicing, stabilization, and translation initiation. Among these regulatory factors, pentatricopeptide repeat (PPR) proteins form the largest family of RNA binding proteins, with hundreds of members in flowering plants. In striking contrast, the genome of the unicellular green alga Chlamydomonas reinhardtii encodes only 14 such proteins. In this study, we analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…Previous research reported that genes belong to subunits of cytochrome were under positive selection in some species 47 , 48 , we therefore inferred that petL for cytochrome b6/f complex subunit proteins may have a high evolution rate in the cp genome of F. luojishanense . The gene rpoC2 was associated with PPR7 protein, we thus speculated it may have coevolved with nuclear genes 49 . The ycf1 and ycf2 are two of the largest genes encoding for a putative membrane protein 50 , 51 and in two Fagopyrum cp genomes these two genes may have rapidly evolved 3 .…”
Section: Discussionmentioning
confidence: 98%
“…Previous research reported that genes belong to subunits of cytochrome were under positive selection in some species 47 , 48 , we therefore inferred that petL for cytochrome b6/f complex subunit proteins may have a high evolution rate in the cp genome of F. luojishanense . The gene rpoC2 was associated with PPR7 protein, we thus speculated it may have coevolved with nuclear genes 49 . The ycf1 and ycf2 are two of the largest genes encoding for a putative membrane protein 50 , 51 and in two Fagopyrum cp genomes these two genes may have rapidly evolved 3 .…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the cemA gene is related to the PPR7 protein. We speculated that cemA may have coevolved with nuclear genes (Jalal et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the nucleus-encoded NAC2 protein is an RNA binding protein with tetratricopeptide-like repeats that stabilizes psbD RNA (Boudreau et al, 2000). Such RNA binding proteins exhibit sequence specificity for a given chloroplast RNA and are encoded by large gene families in land plants that have not yet expanded in algae (Jalal et al, 2015).…”
Section: Chloroplast Biogenesis and Photosynthesismentioning
confidence: 99%